Anemia Pada Remaja Putri Di Desa Mattoangin - Thoban, Eurolita Fitra; Syamsuddin, Fatmawati Annisa; Hariadi, Anisyah (Fakultas Kedokteran Universitas Bosowa, 2025)
Anemia is a condition of decreasing the number of red blood cells in the blood circulation below normal limits and is also a condition when there is a deficiency in the size, number of erythrocytes or hemoglobin content which can cause symptoms often referred to as 5L (lethargic, tired, weak, tired, inattentive). There are several factors that can affect the occurrence of anemia, namely, low iron status due to infrequent consumption of iron food sources (heme and non-heme), poor nutritional status, history of infection and prolonged menstruation. The purpose of the study was to determine the incidence rate of anemia in adolescent females in Mattoangin Village based on (1) nutritional status (2) history of worm infection (3) length of menstruation (4) eating habits. This study was conducted on 99 adolescent females in Mattoangin Village, Bantimurung District, Maros Regency. The research method used in this study is quantitative research with descriptive observational research method with cross-sectional approach, using primary data in the form of interviews using questionnaires and examination of HB levels with Easytouch GCHB tool. Data analysis was processed using SPSS software. The results of this study showed the incidence of anemia and those at risk of anemia in adolescent females in Mattoangin Village: (1) based on the results of the examination of HB levels that fall into the anemia category, namely (33.3%) (2) The most nutritional status is the at-risk category (59.6%), (3) Based on a history of helminth infection at risk of anemia (9.1%), (4) Based on the length of menstruation at risk (14.1%) (5) Based on eating habits at risk (31.3%) The conclusion of the study is that many adolescent females in Mattoangin Village have poor nutritional status and are at risk of anemia.